2009
DOI: 10.1016/j.ultsonch.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate study of the performance of an ultrasound-assisted madder dyes extraction and characterization by liquid chromatography-photodiode array detection

Abstract: An extraction method of madder (Rubia tinctorum) roots dyes is established and optimized to obtain the original chemical composition. A central composite design (CCD) was developed to specify the importance of the three major factors studied (time, temperature and solvent composition) affecting the ultrasound-assisted extraction of this matrix. A preliminary granulometric study of madder roots is realized in the aim to determine the optimal particles size corresponding to the best ultrasound effects. A compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…From previous studies (Cuoco, Mathe, Archier, Chemat, & Vieillescazes, 2009;Garcia-Ayuso & Luque de Castro, 1999;Vilkhu, Mawson, Simons, & Bates, 2008;Wang & Weller, 2006), the particle size was considered one of the important factors that can affect the efficiency of polyphenol extraction from orange peels. Thus, preliminary experiments on orange peels of 0.5, 1.0, 1.5, 2.0 and 2.5 cm 2 gave final yields of 3.44%, 3.65%, 4.32%, 4.41% and 4.38%, respectively.…”
Section: Influence Of Particle Sizementioning
confidence: 99%
“…From previous studies (Cuoco, Mathe, Archier, Chemat, & Vieillescazes, 2009;Garcia-Ayuso & Luque de Castro, 1999;Vilkhu, Mawson, Simons, & Bates, 2008;Wang & Weller, 2006), the particle size was considered one of the important factors that can affect the efficiency of polyphenol extraction from orange peels. Thus, preliminary experiments on orange peels of 0.5, 1.0, 1.5, 2.0 and 2.5 cm 2 gave final yields of 3.44%, 3.65%, 4.32%, 4.41% and 4.38%, respectively.…”
Section: Influence Of Particle Sizementioning
confidence: 99%
“…The limitations of conventional methods such as high solvent requirement, low quality of extract, huge time consumption, and possible thermal decomposition of target molecules paves the way for the emergence of novel extraction techniques for herbals (Luque de Castro & Garcia-Ayuso 1998). The various techniques have been developed to overcome such limitations like microwave assisted extraction (MAE), ultrasound assisted extraction (UAE), supercritical fluid extraction (SFE), accelerated solvent extraction (ASE), enzyme assisted extraction (EAE), and pressurized liquid extraction (PLE) (Cuoco et al 2009;Devgun et al 2009;Gao et al 2010;Hossain et al 2011;Mustafa & Turner 2011;Sowbhagya et al 2011). Moreover, these methods can be assumed as 'Green approach' for the extraction of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Natural Red 8. Whilst the aglycon alizarin does occur in planta, it is in much lower concentrations than its glycoside; total glycosides present in R. tinctorum roots are in at least a five-fold concentration over total aglycons, with individual glycoside concentrations significantly higher than their aglycon counterparts [6,8]. The majority of 19th and 20th century literature similarly concluded that the major colorant present in extracts from R. tinctorum was alizarin.…”
Section: Introductionmentioning
confidence: 99%